Final year project assessment system (FYPAS) / Ahmad Jamilizan Muhamad - Muhamad, Ahmad Jamilizan Muhamad (2014)
Currently online systems are dominating the modem information technology which gives many advantages to their users. Final Year Project Assessment System (FYPAS) is developed in order to enhance the current evaluation process that is done manually which is to minimize time and complexity of the evaluation process. The current FYP evaluation processes are paper-based. For that reason, FYPAS is developed in web based platform that run on web server and use web pages as the user interface. Next, all the requirements for assessment system are identified and the system has been developed. In order to gain the best quality and limited time as well, Rapid Application (RAD) is used as project development methodology. RAD objective is to gain advantage of the latest technology available to speed up development process. This system was developed using the Dreamweaver as PHP server scripting platform application, MySQL for the database management system, SQLyog as interface tool for MySQL database interpretation and Apache for the web server. Besides that, this system are mainly contributing to the lecturer (FYP lecturer, supervisor, and examiner) in order easily evaluate student’s project and speed up the marks calculation. It also supports the lecturer in analyzing student’s result where the system provides the detail of the result features. Next, the evaluation has been done with 20 respondents consists of FYP lecturer, supervisor and examiner to evaluate the system usability. The construct with the highest result is regarding the interface with 69% respondents agree with the interface design and mode for this construct is 4. The highest mean based on user feedback for this construct is item code B2 (mean = 4.05, SD = 0.6048). This indicates that, the respondents are agreed with the interface element for this system. In future, this system can be changes in term of interfaces and functionality in order to improve the reliability and the performances of the system.